2009
DOI: 10.1167/9.6.1
|View full text |Cite
|
Sign up to set email alerts
|

Long-lasting modulation of feature integrationby transcranial magnetic stimulation

Abstract: The human brain analyzes a visual object first by basic feature detectors. On the objects way to a conscious percept, these features are integrated in subsequent stages of the visual hierarchy. The time course of this feature integration is largely unknown. To shed light on the temporal dynamics of feature integration, we applied transcranial magnetic stimulation (TMS) to a feature fusion paradigm. In feature fusion, two stimuli which differ in one feature are presented in rapid succession such that they are n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
109
1
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(129 citation statements)
references
References 59 publications
16
109
1
3
Order By: Relevance
“…Hence, information persistence in a buffer stage might explain why Prime 2 remains dominant even when Prime 1 has a head start long enough to provoke a high rate of response errors under conditions of speeded instead of delayed responding. Such a twostage model was recently proposed for decision making (Rüter, Marcille, Sprekeler, Gerstner, & Herzog, 2012;Rüter, Sprekeler, Gerstner, & Herzog, 2013;Scharnowski, Hermens, Kammer, Ogmen, & Herzog, 2007) and is supported by transcranial magnetic stimulation experiments, which show that vernier fusion takes up to 400 ms (Rüter, Kammer, & Herzog, 2010;Scharnowski et al, 2009).…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Hence, information persistence in a buffer stage might explain why Prime 2 remains dominant even when Prime 1 has a head start long enough to provoke a high rate of response errors under conditions of speeded instead of delayed responding. Such a twostage model was recently proposed for decision making (Rüter, Marcille, Sprekeler, Gerstner, & Herzog, 2012;Rüter, Sprekeler, Gerstner, & Herzog, 2013;Scharnowski, Hermens, Kammer, Ogmen, & Herzog, 2007) and is supported by transcranial magnetic stimulation experiments, which show that vernier fusion takes up to 400 ms (Rüter, Kammer, & Herzog, 2010;Scharnowski et al, 2009).…”
Section: Discussionmentioning
confidence: 79%
“…We know that such fusion occurs when the prime sequence is presented without the target because participants cannot report whether the first or second vernier is offset (Scharnowski et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, processing and extracting relevant information from visual input is a highly complex process that can take up a considerable amount of time. Recent studies have shown that it can take up to almost 400 msec before visual information is available for conscious report (e.g., Scharnowski et al, 2009;Heinen, Jolij, & Lamme, 2005). It is therefore not surprising that reacting to external events does not require awareness of those events.…”
Section: Introductionmentioning
confidence: 99%
“…Embora ainda em uso por pesquisadores (27)(28)(29)(30)(31), sua fabricação e comercialização está descontinuada, não existindo um substituto no mercado.…”
Section: Gerador De Estímulos Visuais Desenvolvido -Vsimgunclassified